Efeitos da estatina como coadjuvante ao tratamento convencional da doença periodontal induzida em ratos - Santos, Bianca Fernanda Espósito (2016)
The objective of this study was to evaluate the local effects of statins as adjuvant treatment of scaling and root planing of periodontal disease induced in rats. The sample of the survey universe was composed for thirty-six (36) mice were divided into 2 groups of 18 animals each. Periodontal disease was induced in all animals using a cotton yarn placed in the region dento - gingival left of the first molars. After 7 days of induction, the ligature was removed, and the animals were divided into two groups according to the following local treatments: Control Group (C) - scaling and root planing (SRP) and with irrigation control gel; Simvastatin Group (S) - and RAR irrigation gel simvastatin. In each group 6 animals were euthanized at 7, 15 and 30 days post local treatments. Samples of gingival biopsies were processed with ligation region for analysis of expression of Matrix metalloproteinase 8 (MMP-8). The jaws were removed and sectioned in half to radiographic and laboratory subsequently processed for histometric analysis. It was observed that the group C had a significantly higher MMP-8 expression compared to the S group in all experimental periods. The expression of MMP-8 intra groups, the animals of both groups showed a significantly higher expression than 7 to 30 days. In the radiographic and histometric analysis between the groups, the group C showed a bone loss (PO) significantly higher compared to the S group in all experimental periods. In radiographic intra groups, group C had a significantly higher PO at 7 days than at 30 days. Within the limits of this study, it can be concluded that Statin applied locally was effective as adjuvant treatment to the SRP induced periodontal disease in rats.